Thyroid Tumour Scanning with 197HgCl2 Preliminary Note - Artagaveytia, Daniel; Degrossi, Osvaldo J.; Pecorini, Victorio (Nuklearmedizin - NuclearMedicine, 1970)
Thirteen patients with cold thyroid nodules were scanned after the administration of 197HgCl2. All nodules were examined histologically. Of the 8 nodules which had concentrated the radionuclide, 7 proved to be carcinomatous and one to be a foetal adenoma. The remaining 5 nodules with a negative scan were all colloid adenomata. These findings suggest that 197HgCl2 may be a valuable scanning agent for the detection of malignant tumours.